Preparation of Second Generation Ionic Liquids by Efficient Solvent-Free Alkylation of N-Heterocycles with Chloroalkanes - Werner Bonrath; Julien Estager; Jean-Marc Lévêque; Luisa Boffa; Emanuela Calcio Gaudino; Giancarlo Cravotto (Molecules, 2008)
Non-conventional techniques, such as microwave (MW) and power ultrasound(US) as well as combined MW/US irradiation, have been used to promote one-potsynthesis of second-generation ionic liquids (ILs), cutting down reaction times andimproving yields. However, the use of chloroalkanes in the alkylation of N-heterocyclesrequires more drastic conditions if results are to match those obtained with more reactivealkyl halides. The present paper describes a series of MW- or MW/US-promoted ILpreparations starting from chloroalkanes and classic heterocycles (1-methylimidazole,pyridine and 1-methylpyrrolidine). When reactions were carried out under conventionalheating in an oil bath they required longer reaction times and gave poorer yields. 1H-NMRanalysis and ion-exchange chromatography showed that the present solventless procedureafforded ILs of satisfactory purity. The observed high yields (usually 70-98% isolated),and short reaction times showed that a straightforward access to ILs can be also achievedwith the use of alkyl chlorides, resulting in a considerable reduction of costs.